Komunikasi Jin dalam Mempengaruhi Manusia Menurut Al-Qur’an: Studi Analisis di Rumah Sehat Aceh, Indonesia - Muhamad Taki Rumakat; Fauzi Saleh; Abizal Muhammad Yati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Jinns are creatures with the same obligation as humans, worshiping Allah (God). In general, there are two kinds of jinn: evil jinn (Satan/kuffar) and Muslim jinn. The primary duties of evil jinn include persuading humans to spread hate, killing, and other evil acts. One of the ways that evil jinn do to achieve their goals is by possessing humans. In this study, the concern was to investigate how jinn communicated affecting humans and how to solve possession by jinn at Rumah Sehat Aceh. The method used to analyze the data was descriptive analysis with the qualitative approach. The results showed that at Rumah Sehat Aceh, communication with the jinn was done during the possession state. There were two types of communication: verbal and non-verbal. However, most jinns lied during communication; therefore, the patients’ families who also listened to the communication between the jinn and the person performing an exorcism (ruqyah) should not consider the jinn utterances as feedback for the cause of the disease because the jinn might be trying to influence them to sway from Allah. In addition, the procedures in dealing with jinn possession at Rumah Sehat Aceh were the exorcist first took wudu (ablution), performing sunnah/voluntary prayers at duha (forenoon), and also giving advice regarding amar ma’ruf nahi munkar (enjoining good and forbidding wrong).